ANALISIS KEPUASAN KERJA, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT SUMBER ALFARIA TRIJAYA Tbk AREA MEDAN TUNTUNGAN - OK Dilla Syahputra; Lubis, Hidayati Purnama (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study was to investigate the effects of work motivation, job satisfaction, and the non-physical work environment on employee performance at PT Sumber Alfaria Trijaya Tbk, which is situated in the Medan Tuntungan Area. Associative, quantitative research methodology was applied. Using a census sampling technique, all 46 employees participated in the survey as respondents. Questionnaires were used to collect data, and SPSS version 24 was used for processing. Multiple linear regression was used to analyze the data for the study, which was conducted between October 2024 and March 2025. The findings showed that work motivation, job happiness, and the non-physical work environment all significantly and favorably impacted employee performance on both an individual and group level. Hypotheses H1, H2, H3, and H4 were so validated. With the highest t-value of 4.896, work motivation was shown to be the most significant of the three independent variables. The three variables taken together explained 93.8% of the variance in employee performance, indicating a high relationship between performance and the independent variables under investigation.